TECHNOLOGY ETHICS IN HANDLING CONFIDENTIAL INFORMATION FOR THE ARMED FORCES - Nor Azreen Zakaria, 1986-, author; Zuraini Ismail, Assoc.Prof.Dr., supervisor; Sekolah Informatiks Termaju (Kuala Lumpur : Universiti Teknologi Malaysia, 2015)
Thesis (Sarjana Sains (Jaminan Maklumat))-Universiti Teknologi Malaysia, 2015